2015
DOI: 10.1002/glia.22892
|View full text |Cite
|
Sign up to set email alerts
|

CCL11 enhances excitotoxic neuronal death by producing reactive oxygen species in microglia

Abstract: The chemokine CCL11 (also known as eotaxin-1) is a potent eosinophil chemoattractant that mediates allergic diseases such as asthma, atopic dermatitis, and inflammatory bowel diseases. Previous studies demonstrated that concentrations of CCL11 are elevated in the sera and cerebrospinal fluids (CSF) of patients with neuroinflammatory disorders, including multiple sclerosis. Moreover, the levels of CCL11 in plasma and CSF increase with age, and CCL11 suppresses adult neurogenesis in the central nervous system (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 66 publications
3
87
1
Order By: Relevance
“…Specifically, there was significant elevation of IL-1α, IL-1β, IL-3, IP-10, IL-5, TGFβ, IL-12 (p40), IL-12 (p70), IL-17, IL-13, RANTES, IFNγ, GM-CSF, TNFα, MIP-1α, MCP-3, EOTAXIN, and MCP-1 levels within the infarct of the stroked mice compared to the equivalent area of the cortex in sham mice. Of these, IL-1, IP-10, IL-17, IL-13, IFNγ, TNFα, EOTAXIN, and MCP-1 (CCL2) have all been linked to cytotoxicity in neurons (Gelbard et al, 1993; Sui et al, 2006; Takeuchi et al, 2006; Thornton et al, 2006; Mizuno et al, 2008; Tzartos et al, 2008; Park et al, 2009; Shichita et al, 2009; Yang et al, 2011; Kang et al, 2012; Parajuli et al, 2015) (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Specifically, there was significant elevation of IL-1α, IL-1β, IL-3, IP-10, IL-5, TGFβ, IL-12 (p40), IL-12 (p70), IL-17, IL-13, RANTES, IFNγ, GM-CSF, TNFα, MIP-1α, MCP-3, EOTAXIN, and MCP-1 levels within the infarct of the stroked mice compared to the equivalent area of the cortex in sham mice. Of these, IL-1, IP-10, IL-17, IL-13, IFNγ, TNFα, EOTAXIN, and MCP-1 (CCL2) have all been linked to cytotoxicity in neurons (Gelbard et al, 1993; Sui et al, 2006; Takeuchi et al, 2006; Thornton et al, 2006; Mizuno et al, 2008; Tzartos et al, 2008; Park et al, 2009; Shichita et al, 2009; Yang et al, 2011; Kang et al, 2012; Parajuli et al, 2015) (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…In primary cell lines obtained from mice, treatment with exogenous CCL11 increases microglial migration and induces the production of microglial reactive oxygen species, directly contributing to neuronal death in co-culture systems [18]. Previous studies have shown that serum CCL11 levels rise acutely in a mouse model of traumatic brain injury [8].…”
Section: Discussionmentioning
confidence: 99%
“…Both AOPP and MDA may be also marked in erythrocytes [74, 75]. Furthermore, the following are also measured in the CSF: levels of MDA and IsoP [54, 76, 77], ceramides [78], chemokine 11 (CCL11) [79], AOPP, and a decreased level of total thiol groups [80]. …”
Section: The Importance Of Os In Msmentioning
confidence: 99%